Identification of Lr-genes in the breeding lines of spring soft wheat, tolerant to the pathogen of brown rust in the Central Black earth region - Yu. V. Zeleneva; V. V. Plakhotnik; V. P. Sudnikova (Зерновое хозяйство России, 2018)
Yu.V. Zeleneva, Candidate of Agricultural Sciences, senior research associate; V.V. Plakhotnik, Candidate of Biological Sciences, head of the laboratory; V.P. Sudnikova, Candidate of Agricultural Sciences, senior research associate Middle-Russian Branch of FSBSI ‘Tambov RIA’ (392553, Tambov region, Tambov district, v. of Novaya Zhizn, Molodezhnaya Str., 1; tel.: 8(4752)62-90-60, e-mail: tmbsnifs@mail.ru) Identification of Lr-genes in the breeding lines of spring soft wheat, tolerant to the pathogen of brown rust in the Central Black earth region The research showed that the direct introduction of the donors of other regions into the breeding process do not always give a desired result because of the weak adaptive ability of the following generations. The development of highly efficient genetic sources and donors adapted to the regional conditions and possessing a complex of positive traits and properties (e.g. group and/or complex tolerance to stress factors of environment) is of special importance, in order not to damage the balance of associated genes among wheat varieties in the CNeR and to increase breeding results. The molecular markers have been applied to identify Lr-genes in 79 breeding lines of wheat, grown in the Middle-Russian branch of FSBSI ‘Tambov RIA’. The wheat lines combined tolerance to brown rust and other positive traits, e.g. resistance to stem pests, drought tolerance, high productivity, and technological quality of grain. The molecular analysis of the material identified single Lr-genes as well as the combination of several genes with different efficiency in one genotype. Among the studied material the Lr9, Lr10, Lr19, Lr20, Lr24, Lr26 and Lr34 genes have been found. There were a lot of lines with the Lr19 gene in a combination with Lr10, Lr20 and Lr26 genes in one genotype.